2018
DOI: 10.1039/c8sc01799a
|View full text |Cite
|
Sign up to set email alerts
|

A photochemical layer-by-layer solution process for preparing organic semiconducting thin films having the right material at the right place

Abstract: A mild and versatile solution process enables the controlled preparation of multicomponent organic small-molecule thin films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 43 publications
(36 reference statements)
0
18
0
Order By: Relevance
“…The three‐layer device can maintain the effective dissociation of excitons, while improving the efficiency of charge transport and extraction, so that a PCE of 4.7% is obtained. [ 16 ]…”
Section: Methods To Improve the Performance Of Lbl Solution‐processedmentioning
confidence: 99%
See 1 more Smart Citation
“…The three‐layer device can maintain the effective dissociation of excitons, while improving the efficiency of charge transport and extraction, so that a PCE of 4.7% is obtained. [ 16 ]…”
Section: Methods To Improve the Performance Of Lbl Solution‐processedmentioning
confidence: 99%
“…[10][11][12] Compared with BHJ, the LbL solution processing method with many advantages is a cost-effective alternative way. [13][14][15][16] Firstly, good contact between the material and the corresponding electrodes can be ensured by sequentially spin coating materials. Second, LbL solution-processed OSCs could optimize the donor layer and acceptor layer separately to make the two components ideally distribute in the vertical direction.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum benefit of this structure can be gained by optimizing each sublayer in terms of material, morphology, and thickness. As a proof of this concept, we have demonstrated that a ternary p-i-n OPV can achieve a power-conversion efficiency (PCE) almost twice as high as the corresponding simple bulk-heterojunction (BHJ) device (5.9 vs. 3.0%) [20].…”
Section: Introductionmentioning
confidence: 97%
“…One of the remaining challenges with the photoprecursor approach is establishing moleculardesign principles for highly effective, robust p-sublayer (or hole-transport) materials. The compounds employed in our previous studies (2,6-di(thiophen-2-yl)anthracene (DTA) and 2,8diphenylanthra[1,2-b:5,6-b']dithiophene (PhBADT), Figure 2) are not ideal in that they are strongly aggregating and form highly rough surfaces [19][20][21]. Indeed, the roughness was too high to determine the effective film thickness, and thus it was not possible to estimate hole mobilities in those materials by the space-charge-limited-current (SCLC) method.…”
Section: Introductionmentioning
confidence: 99%
“…[43][44][45][46][47][48][49][50][51][52] Since the conversion of the precursor into the semiconducting material involves a decrease in the solubility owing to the induced structural changes, a three-layered p-i-n structure with the abovementioned vertical-phase separation can be achieved through solution-based processes. [53][54][55][56][57] Here, "i" stands for the interlayer between the p-and n-layers. Similar to the BHJ lm, this layer consists of blended p-and n-type materials.…”
Section: Introductionmentioning
confidence: 99%